Permanent Magnet Tracking Position Sensor - Degang Lv; Ningzhi Jin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In view of the disadvantages of traditional position sensor, a novel permanent magnet tracking position sensor is proposed. The hall component is used to convert the magnetic signal reflecting the shaft velocity and position into an electrical signal by the construction and optimization of magnetic field. And then the resolver-to-digital conversion is carried out by arctangent so as to obtain the signals of shaft position and velocity. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2335